Chlorinated pollutants in blood of White stork nestlings (Ciconia ciconia) in different colonies in Spain. (January 2015) - de la Casa-Resino, Irene; Hernández-Moreno, David; Castellano, Antonio; Pérez-López, Marcos; Soler, Francisco
Highlights: No detected concentrations of PCBs were found in White stork chicks from Extremadura. Agricultural activity and landfills have no influence in the blood levels of OCPs. High levels of OCPs might be associated to migration to the African continent. Abstract: The aim of this study was to investigate the levels of persistent chlorinated pollutants (POPs) in wild birds. The concentrations of multiple POPs, including polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) were determined in plasma of White stork nestlings. Blood samples were collected from three breeding colonies located in the West of Spain that were exposed to different environmental conditions and human activities. The concentrations of PCBs were below the limit of detection in all samples. The OCPs Heptaclor, 4, 4′-DDE, endosulfan and aldrin were detected most frequently in plasma from White stork nestlings. From these four compounds, 4, 4′-DDE and Heptaclor were found in high abundance. OCPs could not be detected in the colony breading nearby a landfill and an intensive agricultural area, indicating that these banned compounds are not taken up by crops growing in this area. However, birds from the colony breading next to a landfill exhibited the highest OCPs levels. These high levels might be due to exposure of the mothers to OCPs during their migration to Africa and subsequent transfer to their eggs.